2013
DOI: 10.1007/s00128-013-1057-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Five Antifouling Biocides on Settlement and Growth of Zoospores from the Marine Macroalga Ulva lactuca L.

Abstract: Antifouling biocides are found in the marine ecosystem were they can affect non-target organisms. In this study the effects of five antifouling biocides on the settlement and growth of Ulva lactuca zoospores were investigated. The biocides investigated were copper (Cu(2+)), 4,5-dichloro-2-n-octyl-3(2H)-isothiazolone (DCOIT), triphenylborane pyridine (TPBP), tolylfluanid and medetomidine. Full concentration-response curves where determined for each compound. EC50 values were determined for copper, DCOIT, TPBP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The results reported here meet or exceed potency estimates previously determined for these compounds against other organisms. For example, polygodial is effective against fungal pathogens at approximately 1 µg mL −1 ( Kubo & Himejima, 1991 ), chlorothalonil kills water fleas and fathead minnows at 0.03–0.2 µg mL −1 ( Sherrard et al, 2002 ), and tolylfluanid controls seaweed zoospores at 0.03 µg mL −1 ( Wendt et al, 2013 ). However, systems that test the bioactivity of compounds in solution must be carefully interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here meet or exceed potency estimates previously determined for these compounds against other organisms. For example, polygodial is effective against fungal pathogens at approximately 1 µg mL −1 ( Kubo & Himejima, 1991 ), chlorothalonil kills water fleas and fathead minnows at 0.03–0.2 µg mL −1 ( Sherrard et al, 2002 ), and tolylfluanid controls seaweed zoospores at 0.03 µg mL −1 ( Wendt et al, 2013 ). However, systems that test the bioactivity of compounds in solution must be carefully interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…During a study of the co-culture of two green algae, Chen et al [38] observed similar differential allelopathic effects; they observed that the growth of Chlorella pyrenoidosa was inhibited by Hydrodictyon reticulatum, with a notable hormetic effect at low concentrations. Wendt et al [39] also reported hormesis in the growth of macroalga Ulva lactuca zoospores induced by low concentrations of a biocide (triphenylborane pyridine). These studies demonstrated that hormetic responses are related to low concentrations of allelochemicals in different algal species.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here meet or exceed potency estimates previously determined for these compounds against other organisms. For example, polygodial is effective against fungal pathogens at approximately 1 µg mL -1 (Kubo and Himejima 1991), chlorothalonil kills water fleas and fathead minnows at 0.03 − 0.2 µg mL -1 (Sherrard et al 2002), and tolylfluanid controls seaweed zoospores at 0.03 µg mL -1 (Wendt et al 2013). However, systems that test the bioactivity of compounds in solution must be carefully interpreted.…”
Section: Discussionmentioning
confidence: 99%